Studi Tentang Profil Konsepsi IPA Guru Sekolah Dasar Menggunakan Three Tier Test - Lutfiah Indriyani; Muslimin Ibrahim; Muhammad Thamrin Hidayat; Sunanto Sunanto (Departement of Mathematics Education, 2023)
Misconceptions are misunderstandings in connecting a concept with other concepts between existing concepts and conceptions that have been understood by the teacher so that the wrong concept is formed and the different conceptions are passed on to students. In order to avoid conceptual errors, it is very important to understand the profile of the conception that occurs in the teacher first. The purpose of this research is to describe elementary school teachers' conception of science on certain science concepts. This study describes the sources of teacher misconceptions that are the cause of teacher misconceptions. The research method used is quantitative descriptive. This research includes exploratory research. In this study using a quantitative approach. The research target was 24 people. The data collection technique is through the Three Tier Test and interviews. The data analysis technique uses the Three Tier Test decision making rubric with percentage calculations then distributed into the conception profile table. Based on the result of research that has been done shows that the teachers’ conception of Yapita Surabaya Elementary School students had misconceptions about certain science concepts by 12.04% of the 20 concept items answered while teachers who understood the concepts were only 5.41% and conceptions that did not understand by 2.54%. Sources of conceptual errors in teachers that are the cause of misconceptions are the teacher’s interaction experience from the surrounding environment, the initial conception does not master the concept, and the textbook media used is not relevant to the concept. Thus it can be concluded that there is a misconception in the teacher’s conception caused by a concept that is misunderstood so that it is not in accordance with the facts